2012
DOI: 10.1017/s0033291712001432
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of diagnostic specificity in the neural correlates of facial affect processing in bipolar disorder and schizophrenia: a meta-analysis of functional imaging studies

Abstract: During facial affect processing, patients with BD show overactivation in subcortical regions and underactivation in prefrontal regions of the facial affect processing network, consistent with the notion of reduced emotional regulation. By contrast, overactivation within visual processing regions coupled with reduced engagement of facial affect processing regions points to abnormal visual integration as the core underlying deficit in SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 100 publications
(121 reference statements)
6
106
1
Order By: Relevance
“…Interestingly, a recent meta-analysis of fMRI studies employing facial emotion tasks found no effect of gender, but age correlated with higher, and increased symptom severity with lower, parahippocampal gyrus activity [27]. The use of explicit (affect labelling) and implicit (age/gender discrimination) tasks varied across studies.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent meta-analysis of fMRI studies employing facial emotion tasks found no effect of gender, but age correlated with higher, and increased symptom severity with lower, parahippocampal gyrus activity [27]. The use of explicit (affect labelling) and implicit (age/gender discrimination) tasks varied across studies.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Nonetheless, an acceptable proxy may be to survey existing neuroimaging studies of emotion perception in psychosis [15,27,28], and interpret their findings within the context of attentional and interpretative biases. Facilitating this interpretation is a model of aberrant emotion perception in schizophrenia [29].…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning affective face processing are more consistent and have shown that patients demonstrate lower activation in brain regions associated with affective face perception but they show increased activation in areas not associated with face perception [19]. Patients may, therefore, recruit alternative areas to compensate for dysfunction in the key face emotion processing regions.…”
Section: Perception Of Social Cuesmentioning
confidence: 99%
“…These studies have acquired important and useful information that has improved our understanding of the biological basis of schizophrenia and have provided many indices to aid psychiatrists in improving the rates of accurate diagnoses and treatment efficacies [9][10][11][12][13][14][15][16][17]. However, most of these previous studies have focused on exploring the common brain features shared by patients with schizophrenia and depression, these previous studies have provided evidence that structural or functional impairments in some brain regions in patients with schizophrenia overlap with impairments observed in patients with MDD to some extent, The temporal lobe and anterior cingulate are the main affected regions [7,[18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%